2016
DOI: 10.1111/1758-2229.12408
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and adaptation of SAR11 and Cyanobium in a saline Tibetan lake

Abstract: Lake Qinghai is a unique lacustrine ecosystem located on the Tibetan Plateau and exhibits oligotrophic, alkaline, and saline conditions. Previous studies have focused on the community phylogenetic diversity of bacterioplankton in the ecosystem. This study aimed to address the ecotype diversity of bacterioplankton populations in the unique microbial habitat, using metagenomic sequencing and analysis. Phylogenetic analysis revealed two major bacterial populations: SAR11 IIIa (14% of the total) and Cyanobium (14%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The partial genome from Lake Baikal combined with our observations provide robust evidence of SAR11 lineages other than LD12 (SAR11 IIIb) inhabiting freshwater lakes. Prior to these findings, marine SAR11 had been observed in saline lakes (40, 42) and LD12 had been detected and determined to assimilate thymidine in the brackish Gulf of Gdańsk, which is located on the southern Baltic Sea coast and receives freshwater input from the Vistula River (43). The first cultured representative of LD12 was isolated from the coastal lagoon of Lake Borgne (44).…”
Section: Discussionmentioning
confidence: 99%
“…The partial genome from Lake Baikal combined with our observations provide robust evidence of SAR11 lineages other than LD12 (SAR11 IIIb) inhabiting freshwater lakes. Prior to these findings, marine SAR11 had been observed in saline lakes (40, 42) and LD12 had been detected and determined to assimilate thymidine in the brackish Gulf of Gdańsk, which is located on the southern Baltic Sea coast and receives freshwater input from the Vistula River (43). The first cultured representative of LD12 was isolated from the coastal lagoon of Lake Borgne (44).…”
Section: Discussionmentioning
confidence: 99%
“…Genome bins were then obtained based on the metagenome sequence read coverage, occurrence of unique marker genes, and tetranucleotide frequency, using MaxBin as described previously [34]. In contrast to the successful recovery of draft genomes using a similar approach in previous studies [23,32] the genome bins obtained using the metagenomic datasets used in this study showed low genome completeness, unfortunately. Assembling metagenomic data into high-quality genomes can be a complex task, which can be attributable to the inherent biological complexity (e.g., intra-species level genomic diversity and mobile genetic elements) as well as the highly demanding requirement of computer memory [33].…”
Section: The Core Sar11 Population Is Distinct From Other Marine Counmentioning
confidence: 97%
“…To assess the relative abundance (expressed as coverage) of a SAR11 population, metagenomics reads were searched against the 12 genes (aligned regions) using BLASTn with a cutoff of >70% nucleotide identity and >95 match length. The length of all mapped metagenomic reads was summed and divided by the total length of the 12 genes, as described previously [22][23][24]. The value was subsequently normalized to one Gb of metagenomics sequence, which was expressed as coverage (×).…”
Section: Phylogenetic Identification and Relative Abundance Of Sar11 mentioning
confidence: 99%
See 2 more Smart Citations